Implementation of Cooperation between the City of Surabaya and the City of Kitakyushu in the Development of Waste-to-Energy Technology Based on Waste-to-Energy Power Plants (PLTSa) in 2024-2025 - Ardita Sifana Aulia Amry; Fadhlan Nur Hakiem (Journal of Government Science Studies, 2026)
This study analyzes the implementation of cooperation between the Surabaya City Government and the Kitakyushu City Government in the development of Waste-to-Energy technology based on Waste Power Plants (PLTSa) in the period 2024–2025. The research was motivated by increasing pressure on urban waste management, limited landfill capacity, and the need for a sustainable energy transition. The method used was a descriptive qualitative approach with secondary data obtained through literature studies and official documents. The analysis was conducted using the City-to-City Cooperation concept, which includes four dimensions: free flow of information, reciprocity, mutual understanding, and leadership. The results of the study show that the Surabaya–Kitakyushu cooperation has encouraged information exchange and knowledge transfer in the development of PLTSa, but still faces challenges in the form of technological dependence, institutional capacity limitations, and financing and regulatory constraints. Cooperation is reciprocal, but not yet fully balanced. A shared vision of sustainable development strengthens mutual understanding, while the sustainability of cooperation is further supported by institutional strength. This study concludes that inter-city cooperation plays an important role in the development of Waste-to-Energy in Surabaya, but strengthening local capacity and technological independence are key to the sustainability of the program.